Positive electrode softener, lithium ion battery positive electrode slurry and preparation method
By adding ethylene-acrylate copolymer as a softener to the lithium-ion battery positive electrode slurry to form a homogeneous solution system, the problem of increasing brittleness of the lithium-ion battery positive electrode material under high compaction density is solved, the compaction density and flexibility of the electrode sheet are improved, and the processing yield and safety of the battery are improved.
Patent Information
- Application Number
- CN202411953493.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-21
AI Technical Summary
After the compaction density of existing lithium-ion batteries increases, the brittleness of the electrode sheet increases, making it easy to cause cracks, fractures and difficult electrolyte to soak, which affects the performance and production yield of the battery.
A method for preparing a positive electrode slurry including lithium cobalt oxide, carbon black, polyvinylidene fluoride and ethylene-methyl methacrylate copolymer is used, and a binary, ternary or multi-comprising copolymer of ethylene-acrylate is added thereto as a softener to form a homogeneous solution system to improve the compaction density and flexibility of the electrode sheet.
By adding positive electrode softener, the compaction density and flexibility of the positive electrode sheet are improved, the problems of increased brittleness and poor processing performance are solved, and the processing yield and use safety of the battery are improved.
Smart Images

Figure CN119673973A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery additives, and in particular to a positive electrode softener, a positive electrode slurry for a lithium ion battery and a preparation method thereof. Background Art
[0002] With the widespread application of lithium-ion secondary batteries, lithium-ion batteries are gradually developing in the direction of high capacity and small size. Existing lithium-ion batteries generally use LiCO2 as the positive electrode material active material, and the positive electrode compaction density is about 4.0g / cm 3 In order to increase the capacity of lithium-ion batteries, manufacturers are trying to increase the compaction density of positive electrode materials.
[0003] However, when the compaction density of the positive electrode material with LiCO2 as the active material is increased to 4.1 g / cm 3 When the positive electrode sheet is brittle and above, cracks or even breakage and damage may occur during the production process, and the electrolyte is difficult to penetrate the sheet. This problem greatly reduces the production yield and seriously affects the performance of various battery properties including specific capacity and cycle performance. Similarly, the compaction density of the positive electrode material with LiFePO4 as the active material is increased to 2.4g / cm 3 The same problem occurs when doing the above.
[0004] Patent CN114975939A mentions the use of vinyl or propylene-based water-based polymers to improve the toughness and adhesion of water-based cathodes. However, in the lithium battery industry, water is rarely used as a solvent for positive electrodes. On the one hand, this is because of the stability of water-based adhesives under high voltage of the positive electrode. On the other hand, this is because the density of the positive electrode material is large and there is residual alkali on the surface, which will lead to many negative effects on the positive electrode pulping process and battery performance. Secondly, vinyl or propylene-based water-based polymers are heterogeneous emulsion systems, and their distribution in the battery pole piece is in the form of dots. During the drying process, the emulsion particles will migrate to the surface of the pole piece, so it cannot form a continuous and complete bonding network in the pole piece like a homogeneous solution. This also determines that the heterogeneous system of water-based polymers cannot achieve the ideal toughening and adhesion improvement effect. Summary of the invention
[0005] In view of the above-mentioned problems, the present invention provides a positive electrode softener, a lithium-ion battery positive electrode slurry and a preparation method, aiming to solve the problems of the existing lithium battery positive electrode sheet, such as the low compaction height, the large brittleness of the electrode sheet and a series of processing and electrical performance problems caused by the use of a softener in a heterogeneous aqueous emulsion.
[0006] To achieve the above object, in a first aspect, a method for preparing a positive electrode slurry for a lithium ion battery comprises the following steps: Lithium cobalt oxide, carbon black, polyvinylidene fluoride and ethylene-methyl methacrylate copolymer were weighed in a solid weight ratio of 95:3:1.8:0.2; The polyvinylidene fluoride, the ethylene-methyl methacrylate copolymer and N-methylpyrrolidone are stirred and mixed in proportion to obtain a homogeneous solution system; The lithium cobalt oxide, the carbon black and the homogeneous solution system were stirred and mixed at 30° C. to obtain a positive electrode slurry.
[0007] Wherein, in “the lithium cobalt oxide, the carbon black and the homogeneous solution system are stirred and mixed at 30° C. to obtain a positive electrode slurry”, the positive electrode slurry has a slurry solid content of 70%.
[0008] In the second aspect, a positive electrode softener is used in the method for preparing a positive electrode slurry for a lithium-ion battery as described in the first aspect, comprising any one of binary, ternary, or multi-polymers of ethylene-acrylates, propylene-acrylates, butylene-acrylates, and carbon-carbon double bond-containing olefins-carbon-carbon double bond esters, or a combination of at least two of them.
[0009] In a third aspect, a positive electrode slurry for a lithium-ion battery is prepared by the method for preparing a positive electrode slurry for a lithium-ion battery described in the first aspect, and includes a positive electrode active material, a conductive agent, a binder, a softener, a dispersant, and a dispersion medium; based on the total amount of the positive electrode material, the weight percentage of the positive electrode softener is 0-3%, the weight percentage of the conductive agent is 0.05-5%, the weight percentage of the binder is 1-5%, the weight percentage of the surfactant is 0-2%, and the rest is the positive electrode active material. Compared with not using the positive electrode softener, the solid content of the slurry can be increased by 1-10% after adding the softener.
[0010] Wherein, the positive electrode active material is any one of lithium cobalt oxide, ternary material, lithium iron phosphate, lithium iron manganese phosphate or lithium manganese oxide, or a combination of at least two thereof, wherein the ternary material includes but is not limited to NCM333, NCM523, NCM613, NCM622, NCM811 or NCA; The conductive agent is any one of carbon black, acetylene black, carbon nanotubes, graphite powder, Ketjen black, and carbon fiber, or a combination of at least two thereof; The binder is any one of polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, polyimide, hydrogenated nitrile rubber, polyacrylate or polyvinyl alcohol, or a combination of at least two thereof; The dispersion medium includes any one of NMP, methanol, ethanol, ethylene glycol, isopropanol, DMA, DMF, and DMSO, or a combination of at least two thereof.
[0011] The invention discloses a method for preparing positive electrode slurry for lithium ion batteries, comprising the following steps: weighing lithium cobalt oxide, carbon black, polyvinylidene fluoride and ethylene-methyl methacrylate copolymer according to a solid weight ratio of 95:3:1.8:0.2; stirring and mixing the polyvinylidene fluoride, the ethylene-methyl methacrylate copolymer and N-methylpyrrolidone in proportion to obtain a homogeneous solution system; stirring and mixing the lithium cobalt oxide, the carbon black and the homogeneous solution system at 30° C. to obtain a positive electrode slurry. The softener used in the present invention is a non-crystalline material itself, has a low glass transition temperature, and interacts with polyvinylidene fluoride, a commonly used adhesive for the positive electrode, to reduce the crystallinity of polyvinylidene fluoride. On the other hand, the saturated main chain structure is adsorbed on the surface of the conductive agent, and the interaction between particles caused by high surface energy is weakened through the polymer steric effect, thereby promoting the dispersion of conductive agent materials such as carbon black; furthermore, the softener used in the present invention is a homogeneous solution system. Compared with the softener in the water emulsion system, this homogeneous solution can make the positive electrode softener evenly distributed in the electrode sheet to form a continuous bonding network, thereby better improving the compaction density of the positive electrode sheet, increasing the flexibility of the electrode sheet, and solving the problems of processing and electrical performance such as the large brittleness of the existing lithium battery positive electrode sheet. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0013] Figure 1 It is a comparison result diagram of Example 1, Example 5, Example 6 and Comparative Example 1.
[0014] Figure 2 This is a physical picture of the QTX paint film elasticity tester.
[0015] Figure 3 This is a diagram of the pole pieces of Example 1, Example 5, Example 6 and Comparative Example 1 after passing through a 0.5 mm shaft rod.
[0016] Figure 4 This is a physical comparison diagram of Comparative Example 2 and Example 7.
[0017] Figure 5 It is a comparison diagram of the actual compression results of Comparative Example 3, Example 8 and Example 9.
[0018] Figure 6 It is the distribution diagram of comparative example 1, embodiment 1, embodiment 5 and embodiment 6.
[0019] Figure 7The present invention provides a flow chart of a method for preparing positive electrode slurry for lithium-ion batteries. DETAILED DESCRIPTION
[0020] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0021] See also Figures 1 to 7 In the first aspect, a method for preparing a positive electrode slurry for a lithium-ion battery comprises the following steps: S1 weighed lithium cobalt oxide, carbon black, polyvinylidene fluoride and ethylene-methyl methacrylate copolymer in a solid weight ratio of 95:3:1.8:0.2; Specifically, lithium cobalt oxide (LCO) is used as the positive electrode active material, carbon black (SP) is used as the conductive agent, polyvinylidene fluoride (PVDF) is used as the binder, N-methylpyrrolidone (NMP) is used as the solvent, and ethylene-methyl methacrylate copolymer is used as the positive electrode softener (CSF), and the solid weight ratio is LCO:SP:PVDF:CSF=95:3:1.8:0.2; S2: stirring and mixing the polyvinylidene fluoride, the ethylene-methyl methacrylate copolymer and N-methylpyrrolidone in proportion to obtain a homogeneous solution system; S3: stirring and mixing the lithium cobalt oxide, the carbon black and the homogeneous solution system at 30° C. to obtain a positive electrode slurry.
[0022] The positive electrode slurry has a slurry solid content of 70%.
[0023] The lithium-ion battery positive electrode sheet comprises a current collector and a membrane sheet, and the membrane sheet contains the lithium-ion battery positive electrode slurry.
[0024] Preparation Example 1 Lithium cobalt oxide (LCO) is used as a positive electrode active material, carbon black (SP) is used as a conductive agent, polyvinylidene fluoride (PVDF) is used as a binder, N-methylpyrrolidone (NMP) is used as a solvent, and ethylene-methyl methacrylate copolymer is used as a softener. The polyvinylidene fluoride, the ethylene-methyl methacrylate copolymer and N-methylpyrrolidone are stirred and mixed in proportion according to a solid weight ratio of LCO:SP:PVDF:CSF=95:3:1.8:0.2 to obtain a homogeneous solution system, and then the lithium cobalt oxide, the carbon black and the homogeneous solution system are stirred and mixed at 30°C to obtain a positive electrode slurry with a solid content of 70%.
[0025] Preparation Example 2 Compared with Preparation Example 1, only the softener is replaced by ethylene-ethyl methacrylate from ethylene-methyl methacrylate copolymer.
[0026] Preparation Example 3 Compared with Preparation Example 1, only the softener is replaced by propylene-methyl methacrylate from ethylene-methyl methacrylate copolymer.
[0027] Preparation Example 4 Compared with Preparation Example 1, only the softener is replaced by ethylene-methyl methacrylate copolymer with ethylene-methyl methacrylate:propylene-methyl methacrylate = 1:1.
[0028] Preparation Example 5 Compared with Preparation Example 1, only the ratio of PVDF:CSF was adjusted from 1.8:0.2 to 1.6:0.4.
[0029] Preparation Example 6 Compared with Preparation Example 1, only the PVDF:CSF ratio was adjusted from 1.8:0.2 to 1.4:0.6.
[0030] Preparation Example 7 Compared with Preparation Example 5, only the positive electrode active material is replaced by NCA from LCO.
[0031] Preparation Example 8 Lithium iron phosphate (LFP) is used as a positive electrode active material, carbon black (SP) and carbon tubes (CNT) are used as conductive agents, polyvinylidene fluoride (PVDF) is used as a binder, N-methylpyrrolidone (NMP) is used as a solvent, and ethylene-methyl methacrylate copolymer is used as a softener. According to the solid weight ratio of LFP:SP:CNT:PVDF:CSF=100:1:0.8:1.9:0.1, the polyvinylidene fluoride, the ethylene-methyl methacrylate copolymer and N-methylpyrrolidone are stirred and mixed in proportion to obtain a homogeneous solution system, and then the lithium iron phosphate, the carbon black and the carbon tubes, and the homogeneous solution system are stirred and mixed at 30°C to obtain a positive electrode slurry with a slurry solid content of 60%.
[0032] Preparation Example 9 Compared with Preparation Example 8, only the PVDF:CSF ratio was adjusted from 1.9:0.1 to 1.6:0.4.
[0033] Example 1 The positive electrode slurry obtained in Preparation Example 1 was continuously coated on both sides of the positive electrode current collector aluminum foil, the coated film was dried, and the pole piece was compacted using the extreme rolling parameters to test the maximum compaction that the pole piece can achieve, and the pole piece flexibility test was performed, and then the 4.1 g / cm 3The compacted electrode is prepared and tested for buckle battery: wipe off one side of the positive electrode material, use a buckle battery cutting machine to cut the positive electrode sheet into 14mm diameter membrane sheets, and form a CR2025 buckle battery with the diaphragm, lithium sheet, gasket, and spring to carry out capacity, first efficiency, and rate charge and discharge tests.
[0034] Example 2 Compared with Example 1, except that the positive electrode slurry obtained in Preparation Example 1 is replaced by the positive electrode slurry obtained in Preparation Example 2, the rest is the same as Example 1.
[0035] Example 3 Compared with Example 1, except that the positive electrode slurry obtained in Preparation Example 1 is replaced by the positive electrode slurry obtained in Preparation Example 3, the rest is the same as Example 1.
[0036] Example 4 Compared with Example 1, except that the positive electrode slurry obtained in Preparation Example 1 is replaced by the positive electrode slurry obtained in Preparation Example 4, the rest is the same as Example 1.
[0037] Example 5 Compared with Example 1, except that the positive electrode slurry obtained in Preparation Example 1 is replaced by the positive electrode slurry obtained in Preparation Example 5, the rest is the same as Example 1.
[0038] Example 6 Compared with Example 1, except that the positive electrode slurry obtained in Preparation Example 1 is replaced by the positive electrode slurry obtained in Preparation Example 6, the rest is the same as Example 1.
[0039] Example 7 Compared with Example 1, except that the positive electrode slurry obtained in Preparation Example 1 is replaced by the positive electrode slurry obtained in Preparation Example 7, the rest is the same as Example 1.
[0040] Example 8 Compared with Example 1, except that the positive electrode slurry obtained in Preparation Example 1 was replaced by the positive electrode slurry obtained in Preparation Example 8 and 2.4 g / cm 3 Except for compaction, the rest is the same as Example 1.
[0041] Example 9 Compared with Example 8, except that the positive electrode slurry obtained in Preparation Example 8 is replaced by the positive electrode slurry obtained in Preparation Example 9, the rest is the same as Example 8.
[0042] Comparative Example 1 Compared with Example 1, the only difference is that the positive electrode softener ethylene-methyl methacrylate copolymer is not mixed into the positive electrode slurry, and the solid content of the slurry is only 60%.
[0043] Comparative Example 2 Compared with Example 7, the only difference is that the positive electrode softener ethylene-methyl methacrylate copolymer is not mixed into the positive electrode slurry.
[0044] Comparative Example 3 Compared with Example 8, the only difference is that the positive electrode softener ethylene-methyl methacrylate copolymer is not mixed into the positive electrode slurry.
[0045] Positive electrode sheet limit compaction density test method: Compare Examples 1, 5, and 6 with Comparative Example 1, respectively. The coated positive electrode sheet is rolled three times on a roller press with a 0 gap and a pressure of 25 tons. The compaction density after three compactions is measured. The results are as follows: Figure 1 shown.
[0046] pass Figure 1 It can be seen that compared with Comparative Example 1, the maximum compaction of the electrode sheet is improved by adding a softener to the positive electrode slurry in the embodiments, among which Example 5 has the largest improvement, from 4.14 to 4.36, indicating that the positive electrode softener can improve the positive electrode compaction, and there is an optimal addition range. Adding too much or too little will affect the maximum compaction.
[0047] Evaluation method for the flexibility of positive electrode: Compare Examples 1, 5, and 6 with Comparative Example 1, respectively. The positive electrode sheets subjected to the limit compaction test are tested using a QTX type paint film elasticity tester (such as Figure 2 ) to conduct flexibility test on three shaft rods of 1.5mm / 1.0mm / 0.5mm, and observe and record the pole piece falling, cracking, and creases. The state of the pole piece after passing through the 0.5mm shaft rod is as follows Figure 3 shown.
[0048] pass Figure 3 It can be seen that after the comparative example 1 has passed through a 0.5mm shaft rod, the electrode has obvious creases and a tendency to fall off, while Examples 1 and 6 have creases but no falling off, and Example 5 has basically no creases, indicating that the positive electrode softener can improve the flexibility of the electrode, and there is an optimal addition range. Adding too much or too little will affect the effect.
[0049] pass Figure 4 It can be seen that at the same 3.5 g / cm 3 Under compaction, the electrode sheet of Comparative Example 2 broke directly when passing through the 1.5mm shaft rod, but after adding the positive electrode softener, the electrode sheet of Example 7 had only slight creases and its flexibility was significantly improved.
[0050] pass Figure 5 It can be seen that the maximum compaction of comparative example 3 can only reach 2.5 g / cm 3However, after adding the positive electrode softener, the maximum compaction energy of Example 8 can reach 2.6 g / cm 3 The highest compaction energy of Example 9 is 2.7 g / cm 3 .
[0051] Evaluation of capacity, initial efficiency and rate charge and discharge performance of lithium-ion button batteries: The lithium ion button cells obtained in the above Examples 1 to 9 and Comparative Examples 1 to 3 were tested for capacity, initial efficiency and rate charge and discharge. The test method is as follows: Test temperature: 25℃±2℃ Capacity and first effect test steps: 0.1C / 0.1C Test steps for rate charging: 0.5C discharge, charging at different rates; Test steps for rate discharge: 0.5C charging, discharging at different rates;
[0052] Table 1
[0053] Table 2
[0054] Table 3 It can be seen from Tables 1, 2 and 3 that in the three systems of LCO, NCA and LFP, the capacity and initial efficiency of the button cells are basically the same after adding the positive electrode softener.
[0055]
[0056] Table 4
[0057] Table 5 From the data in Table 4, it can be seen that the battery charging rate and discharge rate performance are slightly improved after adding the positive electrode softener. By comparing Examples 1, 5, and 6, it can be seen that there is an optimal range for the amount of positive electrode softener added. Under this optimal value, the positive electrode softener can exert its maximum effect and achieve the highest charge and discharge rate performance. Figure 6 It can also be seen that the distribution of lithium cobalt oxide and carbon black in the pole piece of Example 5 is the most uniform, which also verifies that there is an optimal addition range for the positive electrode softener. Adding too much or too little will affect the distribution state of the pole piece.
[0058] In the second aspect, a positive electrode softener is used in the method for preparing a positive electrode slurry for a lithium-ion battery as described in the first aspect, comprising any one of binary, ternary, or multi-polymers of ethylene-acrylates, propylene-acrylates, butylene-acrylates, and carbon-carbon double bond-containing olefins-carbon-carbon double bond esters, or a combination of at least two of them.
[0059] In this embodiment, the present invention can improve the compaction density of the positive electrode sheet by adding a proper proportion of softener to the positive electrode slurry of the battery, and at the same time make the positive electrode sheet have good flexibility. The softener itself is a non-crystalline material with a low glass transition temperature, and interacts with polyvinylidene fluoride (PVDF), a commonly used adhesive for the positive electrode, and can reduce the crystallinity of PVDF. On the other hand, the saturated main chain structure is adsorbed on the surface of the conductive agent, and the interaction between particles caused by high surface energy is weakened through the polymer steric effect, which promotes the dispersion of conductive materials such as carbon black, thereby improving the compaction density of the positive electrode sheet, increasing the flexibility of the electrode sheet, and solving the problem of fracture of the positive electrode sheet during processing and use, thereby improving the processing yield and safety of the battery.
[0060] In a third aspect, a positive electrode slurry for a lithium ion battery is prepared by the method for preparing a positive electrode slurry for a lithium ion battery described in the first aspect, comprising a positive electrode active material, a conductive agent, a binder, a softener, a dispersant and a dispersion medium; based on the total amount of the positive electrode material, the weight percentage of the positive electrode softener is 0.1-20%, the weight percentage of the conductive agent is 0.5-10%, the weight percentage of the binder is 0.01-10%, the weight percentage of the surfactant is 0-5%, and the rest is the positive electrode active material.
[0061] The positive electrode active material is any one of lithium cobalt oxide, ternary material, lithium iron phosphate, lithium iron manganese phosphate or lithium manganese oxide, or a combination of at least two thereof, wherein the ternary material includes but is not limited to NCM333, NCM523, NCM613, NCM622, NCM811 or NCA; The conductive agent is any one of carbon black, acetylene black, carbon nanotubes, graphite powder, Ketjen black, and carbon fiber, or a combination of at least two thereof; The binder is any one of polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, polyimide, hydrogenated nitrile rubber, polyacrylate or polyvinyl alcohol, or a combination of at least two thereof; The dispersion medium includes any one of NMP, methanol, ethanol, ethylene glycol, isopropanol, DMA, DMF, and DMSO, or a combination of at least two thereof.
[0062] By comparing Preparation Example 1 and Comparative Example 1, it can be seen that after using the positive electrode softener, the solid content of the lithium cobalt oxide slurry can be increased from 60% to 70%. This is also the beneficial effect of the positive electrode softener in helping the carbon black to disperse. At the same time, this is also a property that the water-phase polymer toughening agent does not have.
[0063] Beneficial effects: 1. The present invention discloses a positive electrode softener, a positive electrode slurry for lithium-ion batteries and a preparation method for improving the flexibility of positive electrode sheets of lithium batteries. Compared with softeners in aqueous emulsion systems, this homogeneous solution system can be evenly distributed in the electrode sheets, helping to disperse conductive agents such as carbon black and forming a continuous bonding network, thereby improving the compaction density of the positive electrode sheets without affecting production efficiency, and improving battery energy density without affecting battery performance.
[0064] 2. The positive electrode softener, positive electrode slurry for lithium-ion batteries and preparation method of the present invention use a non-crystalline material, which has a low glass transition temperature and interacts with polyvinylidene fluoride (PVDF), a commonly used adhesive for positive electrodes, to reduce the crystallinity of PVDF. On the other hand, the saturated main chain structure is adsorbed on the surface of the conductive agent, and the interaction between particles caused by high surface energy is weakened by the polymer steric effect, which promotes the dispersion of conductive materials such as carbon black, thereby improving the compaction density of the positive electrode sheet and increasing the flexibility of the electrode sheet. Within the optimal addition amount range of the softener, this homogeneous positive electrode softener solution system can solve the problem of fracture of the positive electrode sheet during processing and use, thereby improving the processing yield and use safety of the battery.
[0065] The above disclosure is only a preferred embodiment of a positive electrode softener, a positive electrode slurry for lithium-ion batteries and a preparation method of the present invention. Of course, this cannot be used to limit the scope of rights of the present invention. Ordinary technicians in this field can understand that all or part of the processes of the above embodiments and equivalent changes made according to the claims of the present invention still fall within the scope of the invention.
Claims
1. A method for preparing positive electrode slurry for lithium ion batteries, characterized in that: The following steps are involved: Lithium cobalt oxide, carbon black, polyvinylidene fluoride and ethylene-methyl methacrylate copolymer were weighed in a solid weight ratio of 95:3:1.8:0.2; The polyvinylidene fluoride, the ethylene-methyl methacrylate copolymer and N-methylpyrrolidone are stirred and mixed in proportion to obtain a homogeneous solution system; The lithium cobalt oxide, the carbon black and the homogeneous solution system were stirred and mixed at 30° C. to obtain a positive electrode slurry.
2. The method for preparing a positive electrode slurry for a lithium ion battery according to claim 1, characterized in that: In “the lithium cobalt oxide, the carbon black, and the homogeneous solution system are stirred and mixed at 30° C. to obtain a positive electrode slurry”, the positive electrode slurry has a slurry solid content of 70%.
3. A positive electrode softener, used in the method for preparing positive electrode slurry for lithium ion batteries according to any one of claims 1 to 2, characterized in that: It includes any one or a combination of at least two of ethylene-acrylate, propylene-acrylate, butylene-acrylate and binary, ternary or multi-polymers of carbon-carbon double bond-containing olefins and carbon-carbon double bond-containing esters.
4. A positive electrode slurry for a lithium ion battery, prepared by the method for preparing a positive electrode slurry for a lithium ion battery according to any one of claims 1 to 2, characterized in that: It includes positive electrode active material, conductive agent, binder, softener, dispersant and dispersion medium; based on the total amount of positive electrode material, the weight percentage of softener is 0-3%, the weight percentage of conductive agent is 0.05-5%, the weight percentage of binder is 1-5%, the weight percentage of surfactant is 0-2%, and the rest is the positive electrode active material.
5. The positive electrode slurry for lithium-ion batteries according to claim 4, characterized in that: The positive electrode active material is any one of lithium cobalt oxide, ternary material, lithium iron phosphate, lithium iron manganese phosphate or lithium manganese oxide, or a combination of at least two thereof, wherein the ternary material includes but is not limited to NCM333, NCM523, NCM613, NCM622, NCM811 or NCA; The conductive agent is any one of carbon black, acetylene black, carbon nanotubes, graphite powder, Ketjen black, and carbon fiber, or a combination of at least two thereof; The binder is any one of polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, polyimide, hydrogenated nitrile rubber, polyacrylate or polyvinyl alcohol, or a combination of at least two thereof; The dispersion medium includes any one of NMP, methanol, ethanol, ethylene glycol, isopropanol, DMA, DMF, and DMSO, or a combination of at least two thereof.
Citation Information
Cited By
Composite softening agent for lithium battery cylindrical cell pole piece to resist winding fracture and preparation method and application thereof
CN122907583A